Comparison of Different Extraction and Purification Methods of Lime Peel Pectin and Evaluation of Physiochemical, Rheological, and Textural Properties - Baghdadi, Fatemeh; Nayebzadeh, Kooshan; Aminifar, Mehrnaz; Mortazavian, Amir M. (Current Nutrition & Food Science, 2024)
Background: Pectin production has recently attracted considerable research interest due to its various applications arising from its unique characteristics. Lime peel, as a by-product of juice factories, has a promising potential for pectin extraction. Methods: Lime peel pectin samples were extracted by three extraction processes: a) 90°C of heating for 120 min, b) 90°C of heating for 90 min and then 32 min of sonication, and c) 80°C of heating for 60 min and then 22 min of sonication. Then, they were purified either by ethanol or sodium caseinate (SC) and characterized. Results: SC purification did not enhance the pectin yield; rather, it diminished the level of nonpectin components and resulted in purer pectin (i.e., lower sugar content). The samples purified with SC showed much lower viscosity in solution and storage modulus than the samples purified with ethanol, which could be attributed to their lower sugar content and higher pH ( 4.6 vs. 2). However, pectin samples purified with SC had a relatively high sugar gel consistency, maybe due to protein retention in their structure as well as the preferential hydration effect of added sucrose. Conclusion: The compact and extended conformations of the pectin sample, which was extracted by “(c) extraction method” and purified with ethanol, resulted in its high viscosity and storage modulus in solution and the highest gel consistency (16.91 Kg.s) compared to the other samples. Regardless of the conditions of extraction procedures, the purification method had a considerable impact on the pectin samples’ characteristics and potential applications.
Keywords: rheology